ESL and Reluctant Readers Booklist [booklist] - Reynolds, Kate, 1984-; (2008)
ESL and Reluctant Readers Booklist The following titles are recommended for individuals who are learning English as a second language or who aren’t inclined to read. All books are available in the Harold B. Lee Library. The titles are picture books of varying lengths covering a variety of topics, both fiction and nonfiction. This list is ordered according to reading difficulty—the easiest books to read are first, the books with more complex sentence structure and vocabulary are later. Each item includes a Lexile rating—a number which is a measurement of the reading level of the book. For more information on Lexile ratings please visit Lexile's website. Books with higher Lexile ratings are more likely to be text heavy with fewer pictures and include slang or colloquialisms. More titles at specific reading levels can be found by using Lexile’s site to search based on Lexile rating or by grade level. 813 C8812c 2006 Click, Clack, Moo: Cows That Type by Doreen Cronin; pictures by Betsy Lewin. Lexile rating: 160 When Farmer Brown's cows find a typewriter in the barn they start making demands and go on strike when the farmer refuses to give them what they want. 823 G127d The Day I Swapped My Dad For Two Goldfish by Neil Gaiman; pictures by Dave McKean. Lexile rating: 250 After trading his father for two goldfish, a boy and his little sister go on a rollicking adventure around town to get him back. 823 B886wa The Wall by Eve Bunting; illustrated by Ronald Himler. Lexile rating: 270 A boy and his father come from far away to visit the Vietnam War Memorial in Washington and find the name of the boy's grandfather, who was killed in the conflict. 813 M992p Patrol: An American Soldier in Vietnam Walter Dean Myers; collages by Ann Grifalconi. Lexile rating: 280 A frightened American soldier faces combat in the lush forests of Vietnam. 813 N162a Albert by Donna Jo Napoli; illustrated by Jim LaMarche. Lexile rating: 350 One day when Albert is at his window, two cardinals come to build a nest in his hand, an event that changes his life. 811 M6721t To Market, To Market by Anne Miranda; illustrated by Janet Stevens. Lexile rating: 350 Starting with the nursery rhyme about buying a fat pig at market, this tale goes on to describe a series of unruly animals that run amok, evading capture and preventing the narrator from cooking lunch. 398.21 H188g The Girl Who Spun Gold by Virginia Hamilton; illustrated by Leo & Diane Dillon. Lexile rating: 360 In this African American retelling of "Rumpelstiltskin," Lit'mahn spins thread into gold cloth for the king's new bride. 923 K585ra Martin's Big Words: The Life of Martin Luther King, Jr. by Doreen Rappaport; illustrations by Brian Collier. Lexile rating: 410 Picture book biography of the American civil rights leader. 923 C85b Crazy Horse’s Vision by Joseph Bruchac; illustrated by S.D. Nelson. Lexile rating: 420 A story based on the life of the dedicated young Lakota boy who grew up to be one of the bravest defenders of his people. 305.5 B886f Fly Away Home by Eve Bunting; illustrated by Gonald Himler. Lexile rating: 450 A homeless boy who lives in an airport with his father, moving from terminal to terminal and trying not to be noticed, is given hope when he sees a trapped bird find its freedom. Locked Case 927 P445g The Man Who Walked Between the Towers by Mordicai Gerstein. Lexile rating: 480 A lyrical evocation of Philippe Petit's 1974 tightrope walk between the World Trade Center towers. 2004 Caldecott Medal winner for most distinguished picture book. 394.26 N42 L95c Chinatown by William Low. Lexile rating: 520 A boy and his grandmother wind their way through the streets of Chinatown, enjoying all the sights and smells of the Chinese New Year's Day. 813 M983z Zen Shorts by Jon J Muth. Lexile rating: 540 When Stillwater the bear moves into the neighborhood, the stories he tells to three siblings teach them to look at the world in new ways. 813 An245h Handel Who Knew What He Liked by M.T. Anderson; illustrated by Kevin Hawkes. Lexile rating: 550 A man who would later compose some of the world's most beautiful music is shown as a stubborn little boy with a mind of his own. 927 H314k The Dinosaurs of Waterhouse Hawkins : An Illuminating History of Mr. Waterhouse Hawkins, Artist and Lecturer by Barbara Kerley; with drawings by Brian Selznick many of which are based on the original sketches of Mr. Hawkins. Lexile rating: 550 The true story of Victorian artist Benjamin Waterhouse Hawkins, who built life-sized models of dinosaurs in the hope of educating the world about what these awe-inspiring ancient animals and what they were like. 759.13 Ok23w My Name is Georgia : A Portrait by Jeanette Winter. Lexile rating: 580 Presents, in brief text and illustrations, the life of the painter Georgia O’Keefe who drew much of her inspiration from nature 813 B581a Akiak: A Tale From the Iditarod by Robert J. Blake. Lexile rating: 590 Akiak the sled dog refuses to give up after being injured during the Iditarod sled dog race. 895.7 B198p Peacebound Trains by by Haemi Balgassi; illustrated by Chris K. Soentpiet. Lexile rating: 620 Sumi's grandmother tells the story of her family's escape from Seoul during the Korean War, while they watch the trains which will eventually bring her mother back from army service. 928 B171111w The Librarian of Basra: A True Story From Iraq by Jeanette Winter. Lexile rating: 640 Alia Muhammad Baker is a librarian in Basra, Iraq. For fourteen years, her library has been a meeting place for those who love books. Until now. Now war has come, and Alia fears that the library--along with the thirty thousand books within it--will be destroyed forever. 551.5 Sa991s Stars Beneath Your Bed: The Surprising Story of Dust by April Pulley Sayre; pictures by Ann Jonas. Lexile rating: 640 This elegant picture book introduces the concept of dust–what it is, how it travels, and how it stays with us through time. In language both poetic and informative Sayre conveys a sense of wonder at the many small things that make up dust and how it unites people across space and time. 759.13 P765g Action Jackson by Jan Greenberg and Sandra Jordan; illustrated by Robert Andrew Parker. Lexile rating: 650 Imagines Jackson Pollock at work during the creation of one of his paint-swirled and splattered canvasses. 813 W3781222f Freedom on the Menu: The Greensboro Sit-ins by Carole Boston Weatherford; paintings by Jerome Lagarrigue. Lexile rating: 660 The 1960 civil rights sit-ins at the Woolworth's lunch counter in Greensboro, North Carolina, are seen through the eyes of a young Southern black girl. 591.763 M834p Pond by Gordon Morrison Lexile rating: 660 Observes how a glacial pond and the abundance of plants and animals that draw life from it change over the course of a year. 843 Sa22L 2000 The Little Prince by Antoine de Saint-Exupéry; translated from the French by Richard Howard. Lexile rating: 710 An aviator whose plane is forced down in the Sahara Desert encounters a little prince from a small planet who relates his adventures in seeking the secret of what is important in life. 927 R835k Wilma Unlimited: How Wilma Rudolph Became the World’s Fastest Woman by Kathleen Krull; illustrated by David Diaz. Lexile rating: 730 A biography of the African-American woman who overcame crippling polio as a child to become the first woman to win three gold medals in track in a single Olympics. 813 AL277b Behold the Trees by Sue Alexander; illustrated by Leonid Gore. Lexile rating: 770 A land once protected by all sorts of wonderful trees is reduced over time by war and environmental neglect to desert, until new inhabitants plant trees and slowly make Israel bloom again. 927 M694m Mighty Jackie: The Strike Out Queen by Marissa Moss; illustrated by C.F. Payne. Lexile rating: 770 In 1931, seventeen-year-old Jackie Mitchell pitches against Babe Ruth and Lou Gehrig in an exhibition game, becoming the first professional female pitcher in baseball history. 891.8 Si81t The Three Golden Keys by Peter Sis. Lexile rating: 770 Led by a cat on a magical journey through Prague, a man encounters some of the city's landmarks and three traditional Czech fairy tales while trying to find the keys to his childhood home. 927 An24r When Marian Sang: The True Recital of Marian Anderson by Pam Muñoz Ryan; illustrations by Brian Selznick. Lexile rating: 780 An introduction to the life of Marian Anderson, extraordinary singer and civil rights activist, who was the first African American to perform at the Metropolitan Opera and whose life and career encouraged social change. 923 T777r Only Passing Through: The Story of Sojourner Truth by Anne Rockwell; illustrated by R. Gregory Christie. Lexile rating: 790 A powerful biography of one of the abolitionist movement's most compelling voices. Sojourner Truth traveled the country in the latter half of the 19th century, speaking out against slavery. Sojourner's simple yet powerful words helped people to understand the hideous truth about slavery. 813 R983af An Angel for Solomon Singer by Cynthia Rylant; paintings by Peter Catalanotto. Lexile rating: 800 A lonely New York City resident finds companionship and good cheer at the Westway Cafe where dreams come true. 833 B853c The Collector of Moments by Quint Buchholz; translated from the German by Peter F. Neumeyer. Lexile rating: 800 When Max, an artist, departs for a long journey, the boy who is his friend and neighbor visits his apartment and discovers an exhibition of pictures created just for him. 919.8 M3644L The Lamp, The Ice, And a Boat Called Fish: Based on a True Story by Jacqueline Briggs Martin; pictures by Beth Krommes. Lexile rating: 810 Tells the dramatic story of the Canadian Arctic Expedition that set off in 1913 to explore the high north. 940.54 T153a Attack on Pearl Harbor: the True Story of the Day America Entered World War II by Shelley Tanaka; paintings by David Craig; maps by Jack McMaster; historical consultation by John Lundstrom. Lexile rating: 820 Part of the I Was There series, depicts December 7, 1941 from the eyes of four young men who experienced the attack on Pearl Harbor. 927 B446m Snowflake Bentley Jacqueline Briggs Martin; illustrated by Mary Azarian. Lexile rating: 830 A biography of a self-taught scientist who photographed thousands of individual snowflakes in order to study their unique formations. 926 H24641L The Man Who Made Time Travel by Kathryn Lasky; paintings by Kevin Hawkes. Lexile rating: 840 Describes the need for sailors to be able to determine their position at sea and the efforts of John Harrison, an eighteenth century man who spent his life refining instruments to enable them to do this. 811 L86p 2001 The Midnight Ride of Paul Revere by Henry Wadsworth Longfellow; graved and painted by Christopher Bing. Lexile rating: 850 An illustrated version of the narrative poem which describes Paul Revere's midnight ride in 1775 to warn the people of the Boston countryside of an impending attack by the British. 305.892 W831c Coming to America: A Muslim Family’s Story by Bernard Wolf Lexile rating: 870 Depicts the joys and hardships experienced by a Muslim family that immigrates to New York City from Alexandria, Egypt, in the hope of making a better life for themselves. 813 G1837L The Lotus Seed by Sherry Garland. Lexile rating: 880 A young Vietnamese girl saves a lotus seed and carries it with her everywhere to remember a brave emperor and the homeland that she has to flee. 304.8 M268c Coming to America: The Story of Immigration by Betsy Maestro; illustrated by Susannah Ryan. Lexile rating: 890 Illustrated history of immigration. Locked Case 925 D259si The Tree of Life: A Book Depicting the Life of Charles Darwin, Naturalist, Geologist & Thinker by Peter Sis. Lexile rating: 890 Presents the life of the famous nineteenth-century naturalist using text from Darwin's writings and detailed drawings by Sis. 398.22 H666m Merlin and the Making of the King retold by Margaret Hodges from Sir Thomas Malory's Le Morte d'Arthur; illustrated by Trina Schart Hyman. Lexile rating: 910 A retelling of four Arthurian legends, "The Sword in the Stone," "Excalibur," "The Lady of the Lake," and "The Last Great Battle," which feature Merlin, King Arthur, and other familiar figures. 688 W956t Toys! Amazing Stories Behind Some Great Inventions by Don Wulffson; with illustrations by Laurie Keller. Lexile rating: 920 Describes the creation of a variety of toys and games, from seesaws to Silly Putty and toy soldiers to Trivial Pursuit. 630 L584f Fair! By Ted Lewin. Lexile rating: 930 Describes the sights, sounds, and smells of a county fair, from the setting up of the Ferris wheel to the animal, craft, and food judging. 759.5 M582s Michelangelo by Diane Stanley. Lexile rating: 940 A biography of the Renaissance sculptor, painter, architect, and poet, well known for his work on the Sistine Chapel in Rome's St. Peter's Cathedral. 928 Se81k The Boy on Fairfield Street: How Ted Geisel Grew Up to Become Dr. Seuss by Kathleen Krull; paintings by Steve Johnson and Lou Fancher; with decorative illustrations by Dr. Seuss. Lexile rating: 950 Introduces the life of renowned children's author and illustrator Ted Geisel, popularly known as Dr. Seuss, focusing on his childhood and youth in Springfield, Massachusetts. 928 B629c The Daring Nellie Bly: America’s Star Reporter by Bonnie Christensen. Lexile rating: 970 Introduces the life of Nellie Bly who, as a "stunt reporter" for the New York World newspaper in the late 1800s, championed women's rights and traveled around the world faster than anyone ever had. 759.13 R594g Norman Rockwell: Storyteller With a Brush by Beverly Gherman. Lexile rating: 980 Describes the life and work of the popular American artist who depicted both traditional and contemporary subjects, including children, family scenes, astronauts, and the poor. 931 Oc5e The Emperor’s Silent Army: Terracotta Warriors of Ancient China by Jane O’Connor. Lexile rating: 980 Describes the archaeological discovery of thousands of life-sized terracotta warrior statues in northern China in 1974, and discusses the emperor who had them created and placed near his tomb. 923 F85fL Ben Franklin’s Almanac: Being a True Account of the Good Gentleman’s Life by Candace Fleming. Lexile rating: 1000 Brings together eighteenth century etchings, artifacts, and quotations to create the effect of a scrapbook of the life of Benjamin Franklin. 597.3 W154f Fossil Fish Found Alive: Discovering the Coelacanth by Sally M. Walker. Lexile rating: 1000 Describes the 1938 discovery of the coelacanth, a fish previously believed to be extinct and subsequent research about it. 595.79 M341o Outside and Inside Killer Bees by Sandra Markle. Lexile rating: 1010 Whether it’s fear or fascination, most people have strong feelings about bees. Although everyone knows that honeybees are nature’s helpers, who doesn’t get goose bumps at the thought of being attacked by “killer bees”? 973.3 F85s The Signers: The Fifty-six Stories Behind the Declaration of Independence by Dennis Brindell Fradin; illustrations by Michael McCurdy. Lexile rating: 1010 Profiles each of the fifty-six men who signed the Declaration of Independence, giving historical information about the colonies they represented. Includes the text of the Declaration and its history. 952 N145b Shipwrecked! The True Adventures of a Japanese Boy by Rhoda Blumberg. Lexile rating: 1020 In 1841, rescued by an American whaler after a terrible shipwreck left him and his four companions castaways on a remote island, fourteen-year-old Manjiro learns new laws and customs as he becomes the first Japanese person to set foot in the United States. 598.47 W384m My Season with Penguins: An Antarctic Journal by Sophie Webb. Lexile rating: 1040 Describes the author's two-month stay in Antarctica to study and draw penguins. 923 R677fL Our Eleanor: A Scrapbook Look at Eleanor Roosevelt’s Remarkable Life by Candace Fleming. Lexile rating: 1040 Eleanor Roosevelt’s influence on American life in the last century is undeniable. A remarkable perspective on a remarkable woman. 338.5 B627s Six Days in October: The Stock Market Crash of 1929 by Karen Blumenthal. Lexile rating: 1040 A comprehensive review of the events, personalities, and mistakes behind the Stock Market Crash of 1929, featuring photographs, newspaper articles, and cartoons of the day. 398.209415 H35n The Names Upon the Harp: Irish Myth and Legend by Marie Heaney; illustrated by P.J. Lynch. Lexile rating: 1050 Contains eight Irish folktales sampled from the three main cycles of early Irish literature. Introductions to each cycle set the stage for the stories to come. 629.45 T348tm Team Moon: How 400,000 People Landed Apollo 11 on the Moon by Catherine Thimmesh. Lexile rating: 1060 A rare perspective on a story of Apollo11. Includes direct quotes from some who worked behind the scenes along with information from NASA transcripts, national archives, and NASA photos. 974.7 M954b Blizzard: The Storm that Changed America by Jim Murphy. Lexile rating: 1080 Presents a history, based on personal accounts and newspaper articles, of the massive snow storm that hit the Northeast in 1888, focusing on the events in New York City. 923 H287a Hatshepsut, His Majesty Herself by Catherine M, Andronik; illustrated by Joseph Daniel Fiedler. Lexile rating: 1080 A picture book biography of Hatshepsut, a queen in ancient Egypt who declared herself king and ruled as such for more than twenty years. 920.72 K939L Lives of Extraordinary Women: Rulers, Rebels (and What the Neighbors Thought) by Kathleen Krull; illustrated by Kathryn Hewitt. Lexile rating: 1150 Take an entertaining sneak peek behind public personas with this two-volume series of the lives of remarkable people. The text is engaging, lively, and entirely fascinating for readers. Colorful and humorous illustrations highlight bad habits, silly nicknames, strange pets, odd behaviors, and everyday activities 577.5 B47d A Handful of Dirt by Raymond Bial. Lexile rating: 1190 Discusses the nature and importance of soil and the many forms of life it supports. 975.3 C928c Capital by Lynn Curlee Lexile rating: 1220 Provides a history of Washington, D.C., focusing on the National Mall, its monuments and surrounding buildings. Compiled by Kate Reynolds, Farnsworth Juvenile Literature Library, Harold B. Lee Library, Brigham Young University, February 2008. Children's Book and Play Review, February 2008